< TRY AND V >, structure de coordination - Christopher Desurmont (Anglophonia)
This paper attempts to show that the “try and V” construction (V1 and V2) is not simply an informal variant of “try to V”, at least not for those speakers for whom the two constructions are readily available. It is here claimed that the key to an understanding of this construction is the separating function of the coordinator “and”: the transitive verb “try” (V1) is syntactically separated from V2 by the coordinator, and so is being used intransitively, thus acquiring referential autonomy. The verb “try” deprived of a syntactic complement can be paraphrased as “try to do something” and is thus claimed to represent by itself (synthetically and implicitly) the complete set of actions required for the realisation of the coordinated V2 event.